Biodiversity of Gastropods in Intertidal Zone of Krakal Beach, Gunungkidul, Yogyakarta - G. A. B. Y. P. Cahyadi; Ragil Pinasti; Assyafiya Salwa; Maghfira Aulia Devi; Lutfiyah Rizqi Fajriana; Nila Qudsiyati; Pinkan Calista; Rury Eprilurahman (Future Science)
Krakal Beach is located in Gunungkidul Regency, Yogyakarta Special Region. This beach is built by coral reefs. The coral reef is an ecosystem that can support various biota to live on it by being a habitat for many species, such as Molluscs. Mollusc is the phylum that has the most members after Arthropods. Approximately 60,000 living species and 15,000 fossil species belong to Mollusc. The phylum Mollusc is divided into seven classes, one of which is Gastropods. Gastropods are Molluscs that move with their abdominal muscles. Molluscs are so diverse, so this research is aimed to study the biodiversity of Molluscs in the intertidal zone of Krakal beach, Gunungkidul, Yogyakarta. The research was conducted on October 4th, 2019 at 03.10 WIB. The research held when ecological parameters were ±21.3oC for water temperature, ±3.6% for salinity, and 7.5 for pH. The samples were collected using a purposive sampling method, preserved by using a dry preservation method, and identified by determining the morphological characteristics of the shell and referred to many references. This study found 7 families from the class Gastropod in the intertidal zone of Krakal beach, those are Aplustridae, Conidae, Cypraeidae, Mitridae, Muricidae, Nacellidae, and Turbinidae.